From Bricks and Mortar to Bits and Bytes: Examining the Changing State of Reference Services at the University of Toronto Libraries During COVID-19 - Gerbig, Madeline; Holmes, Kathryn; Lu, Mai; Tang, Helen (Partnership, 2021)
Before the pandemic, the University of Toronto was predominantly an in-person experience. The closure of physical libraries and shift to remote learning required library staff and users to adapt to new modes of supporting teaching, learning, and research. A survey was conducted about reference service delivery, staffing models, resources and tools, which asked the respondents to describe reference services at their libraries before and during the pandemic. The objectives of this survey were to capture the state of reference services at the University of Toronto Libraries (UTL), and to compare data about reference practices during the pre-pandemic and pandemic periods with the goal of identifying challenges and opportunities for the future of reference services at UTL. 70% of libraries surveyed used reference desks for reference services pre-pandemic, and during the pandemic, 75% of libraries used virtual reference appointments by video conferencing. The survey results show that reference service staffing and service hours in most surveyed libraries were reduced during the pandemic. Many respondents reported that while they offered fewer reference service hours during the pandemic, they continued to provide assistance outside of scheduled hours. Online tools and platforms that were already familiar to librarians remained popular during the pandemic, allowing service providers to quickly adapt to the virtual environment and ensure seamless service continuity. While the rapid transition in services at the University of Toronto was not without its challenges, it has also offered many new opportunities for re-envisioning reference services at the University of Toronto Libraries.